Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) Mid-year report 2022 - Accelerating Impacts of CGIAR Climate Research for Africa (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project is administered by the Alliance of Bioversity International and the International Center for Tropical Agriculture (CIAT). AICCRA is a project that helps deliver a climate-smart African future driven by science and innovation in agriculture. AICCRA builds on 50 years of CGIAR innovation, AICCRA works to scale climate-smart agriculture (CSA) and climate information services (CIS) that reach millions of smallholder farmers in Africa. AICCRA is already playing a vital catalytic role in strengthening the agricultural research architecture in Africa. Activities financed under AICCRA are being implemented by a broad coalition of CGIAR partners working at the regional, sub-regional, and national levels. AICCRA investments are concentrated in six anchor countries: Ethiopia, Ghana, Kenya, Mali, Senegal, and Zambia, but spillover benefits are being realized in many other ‘spillover’ countries, such as Tanzania, Uganda, Chad, Niger and Nigeria among many more, as AICCRA works with Africa’s regional economic communities (RECs) and their associated regional agricultural research and climate change networks.The AICCRA project runs from early 2021 to 31 December 2023. This is the 2022 mid-year report for AICCRA, providing information on progress and key activities, as well as other topics such as the status of agreements, budget execution, and social and environmental safeguards.